2022
DOI: 10.1002/bse.2969
|View full text |Cite
|
Sign up to set email alerts
|

Is there a trade‐off between environmental performance and financial sustainability in microfinance institutions? Evidence from South and Southeast Asia

Abstract: The environmental performance of microfinance institutions (MFIs) has received considerable attention in recent years. However, the question of whether MFIs' involvement in environmental practices can drive their financial sustainability has yet to be addressed. This is the knowledge gap that we intend to investigate in the current study. Specifically, using a panel of 587 MFI‐year observations for the 2007–2014 period, we investigate whether pursuing proactive environmental strategies, individually and in agg… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
7
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 18 publications
(7 citation statements)
references
References 78 publications
0
7
0
Order By: Relevance
“…Microfinance enterprises' financial sustainability-environmental performance trade-off has been studied. 2022 research on this trade-off in South and Southeast Asia and microfinance companies' financial and environmental dynamics supports this claim [6]. These studies demonstrate how the COVID-19 pandemic and natural catastrophes affect Bangladeshi microfinance, family welfare, financial performance, and sustainability.…”
Section: Literature Reviewmentioning
confidence: 74%
“…Microfinance enterprises' financial sustainability-environmental performance trade-off has been studied. 2022 research on this trade-off in South and Southeast Asia and microfinance companies' financial and environmental dynamics supports this claim [6]. These studies demonstrate how the COVID-19 pandemic and natural catastrophes affect Bangladeshi microfinance, family welfare, financial performance, and sustainability.…”
Section: Literature Reviewmentioning
confidence: 74%
“…To obtain government subsidies, enterprises need to maintain a good relationship with the government and choose the game strategy of welcoming the government, which may induce enterprises to use government subsidies for non-green innovation activities, resulting in resource crowding out of environmental protection activities (Ilinitch et al, 1998). Enterprises that receive government subsidies may have opportunistic behaviors to cater to the government and managers, resulting in the crowding out effect of government subsidies on both green technology innovation and green practical patent innovation, which weaken the environmental performance of enterprises (Ayayi and Wijesiri, 2022). (3) Nonlinear relationship.…”
Section: Environmental Effect Of Government Subsidymentioning
confidence: 99%
“…Employee conduct (EC) embodies acceptable or professional behavior that shows consistent appreciation and consideration of environmental drivers to produce better performance and improved innovation [ 58 ]. Employee conduct and environmental concerns can lessen how negatively company actions affect the environment [ 59 ], while the top management is responsible for educating its employees on the practice of social and environmental responsiveness [ 60 ]. The study of Wang et al [ 28 ] indicated that employee conduct positively impacts the green innovation practices of an organization.…”
Section: Literature Review and Conceptual Frameworkmentioning
confidence: 99%